Correlation between anti-DNA antibody titre and psychiatric manifestations in systemic lupus erythematosus. Issue 614 (December 1976) - Levo, Y.; Kalaci, J.; Pick, A. I.; Golomb, M.
Abstract : A patient with systemic lupus erythematosus with predominant psychiatric involvement was followed during two psychotic exacerbations of her disease. A high correlation was found between disease activity and the titre of anti-DNA antibodies. Disease activity was preceded and accompanied by a high titre, while remission was associated with low titre. The significance of this correlation for the pathogenesis, diagnosis and managment of the psychiatric symptoms of systemic lupus erythematosus are discussed.